The Conflict and Competition among Regional Powers and its Effect on the Region’s Stability: Konflik dan Persaingan Antar Kekuatan Regional dan Pengaruhnya terhadap Stabilitas Kawasan - Aljebori, Saleem F. (Universitas Muhammadiyah Sidoarjo, 2024)
This article explores the longstanding regional animosities and power rivalries among Turkey, Iran, and Saudi Arabia in the Middle East, focusing on their impact on regional peace and stability. Despite extensive research on Middle Eastern geopolitics, there is a need for a comprehensive understanding of how these rivalries shape the region's security dynamics. The study aims to analyze the geopolitical goals driving these powers towards regional dominance, including territorial disputes, religious or ethnic tensions, resource distribution issues, and ambitions to alter the regional structure. Using qualitative analysis of historical and contemporary conflicts, the research highlights how sectarian warfare, proxy wars, and transnational violence contribute to regional instability. The findings reveal that the use of proxies by regional powers exacerbates tensions, leading to humanitarian crises and escalating conflicts. This study underscores the necessity for diplomatic interventions and international cooperation to mitigate the adverse effects of these rivalries on the Middle East's stability. Highlights: Dominance Goals: Driven by territorial, religious, and resource issues. Proxy Wars: Heighten instability and humanitarian crises. Regional Impact: Escalate tensions and threaten peace. Keywords: Middle East, Proxy Wars, Sectarianism, Geopolitical Interests, Destabilization